(3z+1)+(2z-6)=180

Simple and best practice solution for (3z+1)+(2z-6)=180 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3z+1)+(2z-6)=180 equation:


Simplifying
(3z + 1) + (2z + -6) = 180

Reorder the terms:
(1 + 3z) + (2z + -6) = 180

Remove parenthesis around (1 + 3z)
1 + 3z + (2z + -6) = 180

Reorder the terms:
1 + 3z + (-6 + 2z) = 180

Remove parenthesis around (-6 + 2z)
1 + 3z + -6 + 2z = 180

Reorder the terms:
1 + -6 + 3z + 2z = 180

Combine like terms: 1 + -6 = -5
-5 + 3z + 2z = 180

Combine like terms: 3z + 2z = 5z
-5 + 5z = 180

Solving
-5 + 5z = 180

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 5z = 180 + 5

Combine like terms: -5 + 5 = 0
0 + 5z = 180 + 5
5z = 180 + 5

Combine like terms: 180 + 5 = 185
5z = 185

Divide each side by '5'.
z = 37

Simplifying
z = 37

See similar equations:

| N/9+10.36=25.36 | | 6(x-3)=4(x-4)+2(x-1) | | N/6+3=12 | | 2X^2+5X=2X+9 | | 6(x+5)=7x+30 | | 8x+37=8x+13 | | (6z-12)+(5z+16)=180 | | z^2+4z+4+2i=0 | | 1+3(x-5)=7+x | | 0.6a=6 | | (6z-12)+(5z+16)=90 | | 7(x+7)=8x+40 | | 7x+3-5x+84x-1= | | 0.625=0.5r | | (6z+12)+(5z+16)=90 | | N^2-4N-5=0 | | W-4.58=1.78 | | 3/4(t-2)-2/5(2t-3)=3/5 | | 10x-4=8x+1 | | .03n=0.2 | | 4x-1+6x+11=120 | | 8(x+5)=4x+48 | | 8a-6+a-1= | | 8/1/5 | | 4=0.8q | | y=.333(-6) | | y=.333(6) | | 0.2t=9 | | y=.333(0) | | 9/5w=7/9 | | 8=0.6d | | (x/9)+(x/8)=17/72 |

Equations solver categories